Joining of metal-plastic hybrid composites using pre-mixture by laser assisted additive manufacturing process - Shin, Geun Sik; Cha, Eunho; Kang, Dae Young; Jung, Jin Young; Jeong, Hyeondeok; Yu, Siwon; Hwang, Jun Yeon (Elsevier BV, 2025)
Recent studies on metal-plastic bonding have led to growing interest in hybrid 3D printing and joining materials. Until now, most hybrids have focused on printing plastic on metal, excluding metal on plastic. Printing metal on plastic has not been achieved due to significant carbonization of the bottom plastic layer caused by the thermal penetrating of the laser. This research aims to solve this issue by placing a pre-mixture of plastic and metal on the plastic layer. The existing method of laser sintering Ti6Al4V metal on polyethylene terephthalate glycol-modified (PETG) caused mutual permeation between the plastic and metal powders, resulting in a degradation in interfacial adhesion. In contrast, the pre-mixture formed an intermediate interface, preventing the interfacial permeation of powders and suppressing pore formation between the plastic and metal. As a result, the porosity analysis using X-ray tomography shows that the pre-mixture interface effectively suppresses the number of pores between PETG and Ti6Al4V, which is comparatively less than that of the interface without the mixture. This indicates that the pre-mixture strengthens the bond between the plastic and metal while protecting the interface from laser-induced damage.